Closure of orocutanous fistula using a pedicled expanded deltopectoral flap - Balakrishnan, Chenicheri (Pulsus Group Inc, 2008)
Orocutaneous fistulas are associated with considerable morbidity. Closures of these fistulas are a challenge to the reconstructing surgeon. The aim of treatment is to provide healthy tissue to repair both the oral and cutaneous defects. The use of an expanded pedicled deltopectoral flap for the closure of an orocutaneous fistula in a patient who has undergone bilateral neck dissection and radiation is reported.